# A big one!

posted by
**Jen**
.

Using logarithmic differentiate technique, find dy/dx

y = [(x-3)³(x²+1) / (2x+5)³] raised to the power of 1/5

I don't know how to type this. It is the 5th root of all those.

You have

y = [(x-3)³(x²+1) / (2x+5)³]^{1/5}

so

ln y = (1/5)ln([(x-3)³(x²+1) / (2x+5)³] =

(1/5){ln([(x-3)³(x²+1)) - ln(2x+5)³}=

(1/5){3ln(x-3) + ln(x²+1) - 3ln(2x+5)}

Now find dy/dx and exponentiate your result to get the final result.

I hope I read your superscripts right, they're a little small for me.